Inventaritation and Potential Utilization of Macroscopic Mushroom in TPKh Tenjo KPH Bogor - Zalfa Alfatinnisa; Wahyu Aji Mahardhika; Arina Tri Lunggani; Ivan Permana Putra (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The TPKh Tenjo KPH Bogor is a production forest wood collection area and becomes a production forest for the Acacia mangium wood species. Timber harvesting activities leave a lot of tree stumps, twigs, or piles of wood that do not pass production. Environmental conditions with a lot of harvested wood residue and supported by relatively cool air temperatures and high humidity, it is suspected this area has a diversity of macroscopic fungi with various unknown potentials. This study aims to obtain data on the types of macroscopic fungi and their potential uses. The research method includes the stages of exploration, identification and literature study to obtain the potential of the macroscopic fungi found. The research succeeded in finding 8 types of macroscopic fungi classified into the phylum Basidiomycota, 3 orders, 5 families, and 7 genera. The macroscopic fungi include Coprinellus sp., Lentinus sp., Panus sp., Schizophyllum commune, Pycnoporus sp., Fomitopsis sp. 1, Fomitopsis sp. 2, and Lycoperdon sp. Based on the results of the literature study, the potential uses of macroscopic fungi were found are as food, medicine, natural pigment producer, and enzyme producer. This data report can be used as basic information on the use of macroscopic mushrooms by communities around the area to be used as food or medicinal ingredients. Further utilization of this data is the development of the potential of macroscopic fungi that produce enzymes, pigments or drugs to be produced on a large scale. Research on the development of potential mushroom conservation strategies can also be carried out for sustainable use.